Jonathan Harvey's Bhakti for chamber ensemble and electronics: Serialism, electronics and spirituality - Palmer, John (Lewiston Edwin Mellen Press, 1959)
This text provides an analytical study of the serial techniques used by the composer, a discussion about his aesthetics and the correspondence between the music and it's Rig Veda, spiritually inspired meaning.